Osteitis deformans (Paget’s disease) in a Burmese python (Python molurus bivittatus) – A case report - Preziosi, Rosario; Diana, Alessia; Florio, Daniela; Gustinelli, Andrea; Nardini, Giordano (The veterinary journal (1997), 2007)
Osteitis deformans (Paget’s disease of bone) is a chronic focal disorder of bone remodelling characterized by an initial increase in osteoclast-mediated bone resorption, with subsequent compensatory increase in new bone formation, resulting in a disorganized mosaic of woven and lamellar bone. In the Burmese python (Python molurus bivittatus) of this report, multifocal gross swellings involving the proximal third of the vertebral spine were observed and associated with anorexia, a relative inability to move or to fully extend the body, and to strike at prey. Serum biochemistry revealed elevated alkaline-phosphatase activity. Radiographic changes (irregular bone proliferation along the vertebral margins), computed tomography scan results (abnormal mineral density), and histopathological features (generalized thickening of the bony trabeculae at the expense of the intertrabecular spaces and irregular patches of lamellar bone with a characteristic “mosaic” pattern) indicated osteitis deformans.